2015
DOI: 10.15537/smj.2015.1.9774
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of renal replacement therapy and mortality in children with chronic kidney disease

Abstract: Objectives:To study the epidemiology of chronic kidney disease (CKD) in children, and to look for risk factors to predict renal replacement therapy (RRT) and mortality.Methods:This is a retrospective cohort study conducted at King Abdulaziz University Hospital, Jeddah, Saudi Arabia between 2006 and 2014, where the files of 1,000 children with CKD were reviewed. We determined the effect of consanguinity and hypertension, and being a Saudi indigene on mortality and RRT. We compared children with congenital versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…There was a predominance of males, which is in accordance with most studies described in the literature. 4,[9][10][11][12][13][14][15] The median age of the patients was 9.25 years at onset on RRT. This finding is very close to those described in articles on RRT, in Serbia 11 which reported a median age of 9.8 years, in Korea 12 where the median age was 9.7 years, and in Brazil 14 which reported 12.5 years in a more recent study by Konstantyner et al 12 A median age of 13 years was found in India.…”
Section: Discussionmentioning
confidence: 99%
“…There was a predominance of males, which is in accordance with most studies described in the literature. 4,[9][10][11][12][13][14][15] The median age of the patients was 9.25 years at onset on RRT. This finding is very close to those described in articles on RRT, in Serbia 11 which reported a median age of 9.8 years, in Korea 12 where the median age was 9.7 years, and in Brazil 14 which reported 12.5 years in a more recent study by Konstantyner et al 12 A median age of 13 years was found in India.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous observational retrospective study from our center in 2015, 1000 children with CKD were enrolled, the incidence of RRT was 7.7% (hemodialysis 3.6%, peritoneal dialysis 2.6%, and kidney transplantation 1.5%), and bladder dysfunction was the most frequent cause of obstructive uropathy (12.1%). 32 McLeod et al, 33 reported in a multicenter study, 274 children with PUV, who were treated before 90 days and were treated for a median of 6.3 years, 16% progressed to ESKD and required RRT by 10 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of acute and chronic kidney dysfunctions has been the subject of intense discussion, particularly in matters concerning RRT, which includes PD, intermittent and extended HD, and continuous blood purification methods 2 - 4 . Recent studies shed light on the shortage of dialysis supplies in underdeveloped and developing nations 5 .…”
Section: Introductionmentioning
confidence: 99%